Methods for measuring shrinkage - Chapman, Paul; Templar, Simon (Palgrave Macmillan, 2006)
This paper presents findings from research amongst European grocery retailers into their methods for measuring shrinkage. The findings indicate that: there is no dominant method for valuing or stating shrinkage; shrinkage in the supply chain is frequently overlooked; data is essential in pinpointing where and when loss occurs and that many retailers collect data at the stock-keeping unit (SKU) level and do so every 6 months. These findings reveal that it is difficult to benchmark between retailers due to inconsistencies between measurement methods and that there are opportunities for many of the retailers surveyed to improve their shrinkage measurement by adopting known good practice.
Keywords: shrinkage; retail; measurement; survey